Investigate The Influence Of The Fama and French Five-Factor Model On The SRI-KEHATI Stock Index: The Period of 2015–2022 - Dewi, Ayu Oktami; Komara, Esi Fitriani (Jurnal Manajemen Bisnis, 2024)
The capital market functions as an intermediary for the flow of funds between investors and companies, in accordance with the general principle that the greater the risk, the greater the potential profit. In estimating returns, there are several methods, one of which is the Fama French five factor model which was developed from the CAPM, APT and Fama French three factor models. This research aims to evaluate the relationship between the five-factor Fama French model and excess returns on the SRI-KEHATI stock index from 2015 - 2022. This research method adopts quantitative analysis with an associative causality approach and uses a purposive sampling technique to select 9 companies as samples. Data analysis used by Eviews 12. Study findings show that market factors have a significant influence on excess returns, while size, value, profitability and investment factors are not significant on excess returns. Overall, the Fama-French model's five factors collectively influence excess returns. This finding confirms that market conditions will influence the excess returns obtained by investors.